PEMIKIRAN ABU BAKAR ASH-SHIDDIQ TENTANG MEMERANGI ORANG YANG MEMBANGKANG - Shobirin, Shobirin (ZISWAF, 2014)
Zakat is a new thing that is required in nine Hijrah, and the Prophet hadordered to the towing zakat to collect alms from the people who are obliged topay zakat throughout the country. Abu Bakr as the first Caliph Prophet is theone who should be responsible to implement what has been set by the Prophet.